2019
DOI: 10.1002/jor.24522
|View full text |Cite
|
Sign up to set email alerts
|

Sequential CCL2 Expression Profile After Disc Injury in Mice

Abstract: Macrophages produce proinflammatory cytokines in injured intervertebral discs (IVDs). We recently showed that macrophage‐derived inflammatory cytokines contribute to the production of pain‐related factors. However, the mechanism by which macrophages are recruited to injured IVDs has not been fully clarified. Here, we examined the expression dynamics of the chemokine CCL2 in a mouse IVD injury model and the mechanisms of its regulation. The percentage of macrophages increased from day 1 after injury and persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 50 publications
(140 reference statements)
0
14
0
Order By: Relevance
“…Several studies have generated IVD injury models by performing tail puncture under varying conditions [6,[16][17][18][19][20][21][22]. A model in which puncture injury was induced using a 31-gauge needle showed a gradual increase in degenerative score and decrease in glycosaminoglycan levels in IVDs at 6 and 12 weeks post-puncture [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have generated IVD injury models by performing tail puncture under varying conditions [6,[16][17][18][19][20][21][22]. A model in which puncture injury was induced using a 31-gauge needle showed a gradual increase in degenerative score and decrease in glycosaminoglycan levels in IVDs at 6 and 12 weeks post-puncture [22].…”
Section: Discussionmentioning
confidence: 99%
“…We generated an IVD injury model by performing 10 punctures with a 27-gauge needle and found that this model was useful for evaluating increased inflammatory cytokine and growth factor levels, and macrophage recruitment across a short time period of 1 to 28 days. [6,16,18,19] Therefore, we used this model to evaluate the effects of TNF-α and TGF-β on NGF expression.…”
Section: Discussionmentioning
confidence: 99%
“…We examined the expression of Cd11b (macrophage marker), Cd206 (M2 maker), and Tgfb genes, which encode CD11b, CD206, and TGF-β protein, respectively, based on previous reports [9,13,21]. Primers were generated according to our previous report [9,13,21]. The delta-delta Ct method and the housekeeping gene Gapdh were used to determine relative mRNA expression levels of the genes of interest.…”
Section: 3mentioning
confidence: 99%
“…Various kinds of macrophages, including resident macrophages and recruited macrophages, are present in degenerated IVDs [7][8][9][10]. Recruited macrophages differentiate into proinflammatory phenotype M1 macrophages, which are thought to induce inflammation in IVDs [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation